(untitled) (Gestión y Gerencia, 2021)
The knowledge society grows at the speed of technological applications, a product of the consolidation of the fourth industrial revolution and the emergence of the fifth. This has led actors from social and business organizations to develop certain digital skills so as not to detach themselves from these transformations. The objective of this research is to characterize the most important digital skills that organizations have used in the 21st century during these industrial revolutions. The research is of a documentary type, with a qualitative approach, content analysis was used as a method for intentionally selected scientific articles related to proposals for the effect of technology on the skills of workers. The results indicate that for the authors studied, the main characteristics of digital skills in these two industrial revolutions affect the processes and individuals who wish to work with computational tools. It is concluded that, with the emergence of the knowledge and information society, digital skills have been developed in the labor and social force, which have generated opportunities and minimized resistance to change. A triad of fundamental digital skills identified in the two industrial revolutions is proposed: individual soft, individual hard and organizational.